Effect of Transfer Pricing, Capital Intensity and Audit Committee on Tax Avoidance: (Case Study of a Mining Company in the Energy Sector Listed on the Indonesian Stock Exchange for the 2021-2022 Period) - Nori Firdausyah; Moh Halim; Riyanto Setiawan Suharsono (Westscience Press, 2024)
This research was conducted with the aim of providing empirical evidence of Transfer Pricing, Capital Intensity and Audit Committees on Tax Avoidance (Case Study of Energy Sector Mining Companies Listed on the Indonesia Stock Exchange for the 2021-2022 Period). The sample selection technique was carried out using the porpusive sampling method. The total population in this study was 82 companies with a sample size of 31 companies that met the sample criteria. Data collection in this research uses secondary data obtained from the annual financial reports of companies operating in the mining industry, energy sub-sector which are listed on the Indonesia Stock Exchange for the 2021-2022 period. This research method uses a quantitative method with data testing used using SPSS version 26. The data analysis used is descriptive statistical analysis. The results of this research show that transfer pricing, capital intensity, and audit committees have a positive and significant influence on tax avoidance, such as which was tested using t test analysis and F test.